2018
DOI: 10.1039/c7nr08145f
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution localization microscopy of radiation-induced histone H2AX-phosphorylation in relation to H3K9-trimethylation in HeLa cells

Abstract: Ionizing radiation (IR)-induced damage confers functional and conformational changes to nuclear chromatin associated with DNA single and double strand breaks. This leads to the activation of complex DNA repair machineries that aim to preserve the integrity of the DNA molecule. Since hetero- and euchromatin are differentially accessible to DNA repair pathways, local chromatin re-arrangements and structural changes are among the consequences of an activated DNA damage response. Using super-resolution localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(116 citation statements)
references
References 67 publications
9
107
0
Order By: Relevance
“…It has been shown that such foci can be separated into functionally relevant sub-foci or clusters of about the same size independent from the dose applied [23,28,29]. This has also been found for the cell nuclei analyzed here (see Figure S2).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…It has been shown that such foci can be separated into functionally relevant sub-foci or clusters of about the same size independent from the dose applied [23,28,29]. This has also been found for the cell nuclei analyzed here (see Figure S2).…”
Section: Resultssupporting
confidence: 78%
“…The blinking events registered above the fluorescent background are used to compute the exact positions of the individual fluorophores. Tests during former experiments [28,29,34] have revealed that the intensity of the maximum of a point signal must be at least four times higher than the background intensity to get registered as an event. The double of the average background intensity is subtracted from each pixel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations